An Inverse Thermogelling Bioink Based on an ABA-Type Poly(2-oxazoline) Amphiphile - Hahn, Lukas; Karakaya, Emine; Zorn, Theresa; Sochor, Benedikt; Maier, Matthias; Stahlhut, Philipp; Forster, Stefan; Fischer, Karl; Seiffert, Sebastian; Pöppler, Ann Christin; Detsch, Rainer; Luxenhofer, Robert (Biomacromolecules, 2021)
Hydrogels are key components in several biomedical research areas such as drug delivery, tissue engineering, and biofabrication. Here, a novel ABA-type triblock copolymer comprising poly(2-methyl-2-oxazoline) as the hydrophilic A blocks and poly(2-phenethyl-2-oxazoline) as the aromatic and hydrophobic B block is introduced. Above the critical micelle concentration, the polymer self-assembles into small spherical polymer micelles with a hydrodynamic radius of approx 8-8.5 nm. Interestingly, this specific combination of hydrophilic and hydrophobic aromatic moieties leads to rapid thermoresponsive inverse gelation at polymer concentrations above a critical gelation concentration (20 wt %) into a macroporous hydrogel of densely packed micelles. This hydrogel exhibited pronounced viscoelastic solid-like properties, as well as extensive shear-thinning, rapid structure recovery, and good strain resistance properties. Excellent 3D-printability of the hydrogel at lower temperature opens a wide range of different applications, for example, in the field of biofabrication. In preliminary bioprinting experiments using NIH 3T3 cells, excellent cell viabilities of more than 95% were achieved. The particularly interesting feature of this novel material is that it can be used as a printing support in hybrid bioink systems and sacrificial bioink due to rapid dissolution at physiological conditions.
CRIS-Team Scopus Importer:2021-07-02